2014
DOI: 10.3390/ijms150814191
|View full text |Cite
|
Sign up to set email alerts
|

Complete Proteome of a Quinolone-Resistant Salmonella Typhimurium Phage Type DT104B Clinical Strain

Abstract: Salmonellosis is one of the most common and widely distributed foodborne diseases. The emergence of Salmonella strains that are resistant to a variety of antimicrobials is a serious global public health concern. Salmonella enterica serovar Typhimurium definitive phage type 104 (DT104) is one of these emerging epidemic multidrug resistant strains. Here we collate information from the diverse and comprehensive range of experiments on Salmonella proteomes that have been published. We then present a new study of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 104 publications
(87 reference statements)
0
7
0
Order By: Relevance
“…Beyond surveillance studies, our research group has investigated AMR mechanisms by characterizing a range of resistant strains of interest through proteomic approaches in MRSA (Monteiro et al, 2012, 2015) and other bacterial species (Pinto et al, 2010; Radhouani et al, 2010, 2012; Correia et al, 2014, 2016; Goncalves et al, 2014; Ramos et al, 2015, 2016; Monteiro et al, 2016). However, these proteomic studies, and most AMR research in general, have focused on bacteria growing in planktonic cultures and hence overlooked biofilm-specific AMR mechanisms.…”
Section: Preliminary and Expected Resultsmentioning
confidence: 99%
“…Beyond surveillance studies, our research group has investigated AMR mechanisms by characterizing a range of resistant strains of interest through proteomic approaches in MRSA (Monteiro et al, 2012, 2015) and other bacterial species (Pinto et al, 2010; Radhouani et al, 2010, 2012; Correia et al, 2014, 2016; Goncalves et al, 2014; Ramos et al, 2015, 2016; Monteiro et al, 2016). However, these proteomic studies, and most AMR research in general, have focused on bacteria growing in planktonic cultures and hence overlooked biofilm-specific AMR mechanisms.…”
Section: Preliminary and Expected Resultsmentioning
confidence: 99%
“…Likewise, a complete proteome might be obtained through matrix-assisted laser desorption/ionization mass spectrometry (MALDI-TOF MS). Correia et al (2014) reported confirmation of several proteins in S. Typhimurium phage type 104 clinical strain through this method, emphasizing the presence of the Aac(6 0 )-Ib-cr enzyme responsible for both plasmid-mediated aminoglycoside and quinolone resistance [37,57].…”
Section: Investigating Antibiotic Resistancementioning
confidence: 96%
“…The proteome of a fluoroquinolone-resistant S. enterica serovar Typhimurium Se20 isolate (phage type DT104B), recovered after ciprofloxacin treatment, was studied compared to the proteome of a susceptible reference isolate SL1344. In the isolate recovered after antibiotic administration, three proteins related to antimicrobial resistance were detected [ 234 ]. Subsequently, ciprofloxacin-resistant and -susceptible isolates of Salmonella were used and tandem mass tag labelling and acetylation enrichment techniques were employed to screen for the different expression of acetylated proteins between the two isolates and for quantitative and bioinformatics analysis.…”
Section: Proteomics Applications In Antibiotic Resistancementioning
confidence: 99%